(untitled) (Global Journal of Management and Business Research, 2012)
This paper investigates intra-trade and welfare effects for Iran and D-8 countries preferential trade agreement by reviewing the possibility of comprehensive trade liberalization through expanding coverage of preferential tariff reduction. A quantitative analysis is applied for economic effects of a free trade arrangement between Iran and other contracting countries. An important objective of this research is to appraise evidence of significant gains in intra-trade and welfare amongst Iran and D-8 countries when tariff barriers and enhancement measures are dismantled. Therefore, this study uses indices in international trade as an input into the process of evidence-based policymaking in the area of trade policy for D-8 countries.